2020
DOI: 10.1001/jamaophthalmol.2020.2211
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Incidence of Myopic Maculopathy in a General Japanese Population

Abstract: IMPORTANCE Myopic maculopathy is a leading cause of irreversible visual impairment worldwide. Moreover, the burden of myopic maculopathy has been expected to increase owing to the rising prevalence of myopia globally. However, there is limited epidemiologic evidence regarding the incidence of and risk factors for myopic maculopathy. This study from Japan, with a relatively high prevalence of myopia, could provide valuable information related to these issues. OBJECTIVE To estimate the incidence of myopic maculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The most common change of myopic maculopa- Previous studies have shown that compared with individuals with stable fundus, those with myopic maculopathy progression were more likely to have worse BCVA, longer AL, faster AL elongation, and higher myopic SE. 14,16,[20][21][22][23][24] Our results were largely consistent with these publications, except for older age. Interestingly, similar to another investigation focused on the young Chinese population, 11 age did not show an association with the progression of myopic maculopathy in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The most common change of myopic maculopa- Previous studies have shown that compared with individuals with stable fundus, those with myopic maculopathy progression were more likely to have worse BCVA, longer AL, faster AL elongation, and higher myopic SE. 14,16,[20][21][22][23][24] Our results were largely consistent with these publications, except for older age. Interestingly, similar to another investigation focused on the young Chinese population, 11 age did not show an association with the progression of myopic maculopathy in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that age was a risk factor of high myopia, similar findings were reported by Hwang HS 23 and coworkers in a cross-sectional study. Ueda E 24 and coworkers, based on a cohort study, found that older age and longer axial length were associated with the development of myopic maculopathy. Jing S 25 and coworkers also reported that age was positively associated with high myopia.…”
Section: Discussionmentioning
confidence: 99%
“…These associations may reflect the fact that older patients tend to have more extensive pathology and more myopic changes such as MA (Ueda et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%